Quality of Rice Detection Using Machine Earning (International Journal of Innovative Research in Engineering & Management, 2022)
As we all know that rice is the most  consumed food by everyone in our day-to-day life. In rice  manufacturing industries the market demand always depends  on the quality of rice. In verifying the rice quality, the  physical dimensions like length, width and thickness plays a crucial role. Normal methods used for detection of these  factors are time consuming, and not accurate as they are  performed manually. This problem had given the way for  development of computerized vision in rice quality  detection. In the proposed method both image processing and  machine learning techniques are clubbed to analyse and  grade the quality of rice kernels with the help of classifiers in  python platform.
Keywords: Rice quality; Image Processing; Machine learning; Python